The Use and Evaluation of an Inexpensive Eye Model in Direct Ophthalmoscopy Training - Wu, Grace T.; Kang, Jessica M.; Bidwell, Ann E.; Gray, John P.; Mirza, Rukhsana G. (Journal of Academic Ophthalmology, 2014)
Purpose Learning direct ophthalmoscopy to view the fundus is an important skill that is often given insufficient attention in medical school curriculums. The goals of this study were to (1) create an easy-to-assemble, inexpensive artificial eye model, the FAK-I, (2) develop an objective evaluation tool to assess the students' clinical skills in using the direct ophthalmoscopy, and (3) determine if practice with the FAK-I translates into improved clinical examination skills. Methods After an initial hands-on tutorial on direct ophthalmoscopy, study subjects (n = 12) were randomly assigned to a control group (n = 6), which received no FAK-I model, or a study group (n = 6), which received a FAK-I model. After 45 days of no further intervention, students took an objective evaluation of clinical direct ophthalmoscopy skills. Scores of students in the control and study group were compared. Results The study group had a higher percentage of correct responses (44%) compared with the control group (40%), but the difference did not reach statistical significance. More students in the study cohort (50%) reported independently practicing the direct ophthalmoscope than the control group (0%). The study cohort also reported practicing on the FAK-I more frequently than on peers or patients. Conclusions We were able to create the FAK-I, a simple low-cost eye model to practice direct ophthalmoscopy. We also designed an objective evaluation tool to assess students' clinical skills with a direct ophthalmoscope. While the study group scored slightly better than the control group, these numbers did not reach significance due to the limited size of this pilot study. The study group practiced more than the control group, and more often on the FAK-I model than on peers or patients. These findings in this pilot study point to the potential utility of providing a simple eye model in improving direct ophthalmoscopy skills in medical students.
Keywords: educational tools; medical student education; direct ophthalmoscopy; eye model; clinical skills